Professionalism in dental education - Marcela Alcota; Pilar Ruiz-de Gauna; Fermín González (Universidad de Antioquia, 2016)
Several authors as well as professional and educational institutions have advanced the issue of professionalism in the field of dentistry, agreeing that, even though professionalism plays a central role in the training of dentists, its incorporation in the curriculums of dental schools worldwide is limited. Therefore, graduates have poor training in dental professionalism. This review article will analyze the concepts of crossdisciplinary skills, such as professional values and the formation of professionalism in different areas during the dental career, with the purpose of highlighting the importance of these aspects in the training of dentistry students and, on the other hand, the responsibility of educational institutions in providing students with such training.